Coexpressing the Signal Peptide of Vip3A and the Trigger Factor of Bacillus thuringiensis Enhances the Production Yield and Solubility of eGFP in Escherichia coli - Gao, Jianhua; Ouyang, Chunping; Zhao, Juanli; Han, Yan; Guo, Qinghua; Liu, Xuan; Zhang, Tianjiao; Duan, Ming; Wang, Xingchun; Xu, Chao (Frontiers in Microbiology, 2022)
Many fusion tags have been developed to improve the expression of recombinant proteins. Besides the translocation of cargo proteins, the signal peptides (SPs) of some secretory proteins, such as the ssTorA and Iasp, have been used as inclusion body tag (IB-tag) or the recombinant expression enhancer in the cytosol of E. coli. In this study, the approach to utilize the SP of Vip3A (Vasp) from Bacillus thuringiensis (Bt) as a fusion tag was investigated. The results showed that either the Vasp or its predicted N- (VN), H- (VH) and C-region (VC), as well as their combinations (VNH, VNC and VHC) were able to significantly enhance the production yield of eGFP. However, the hydrophobic region of the Vasp (VH and/or VC) made more than half of eGFP molecules aggregated (VeGFP, VHeGFP, VCeGFP, VNHeGFP, VNCeGFP and VHCeGFP). Interestingly, the addition of Bt trigger factor (BtTF) led to the neutralization of the negative impact and solubilization of the fusion proteins. Therefore, the coexpression of Vasp or its derivates with the chaperone BtTF could be a novel dual-enhancement system for the production yield and solubility of recombinant proteins. Notably, EcTF was unable to impact the solubility of Vasp or its derivates guided proteins, suggesting its different specificity on the recognition or interaction. Additionally, the present study also suggested that the translocation of Vip3 in the host cell would be regulated by the BtTF involved model.